Analysis of the Impact of Tax Planning on Corporate Profitability - Loso Judijanto; Yulianti Yulianti; Fitriani Fitriani (Oikonomia : Journal of Management Economics and Accounting, 2026)
This study examines how tax planning influences corporate profitability by considering both direct financial effects and the indirect mechanism through firm growth. In the context of increasing regulatory scrutiny and strategic financial management, tax planning has shifted from a compliance function to a managerial decision that potentially enhances firm performance. Using a quantitative explanatory design, this research analyzes panel data from publicly listed non-financial firms based on secondary data derived from audited financial statements. Tax planning is proxied by Effective Tax Rate (ETR) and Cash Effective Tax Rate (CETR), profitability is measured by Return on Assets (ROA), and Firm Size is tested as a mediating variable. Panel regression and Sobel mediation tests are employed to examine the relationships among variables. The findings indicate that ETR and CETR significantly affect Firm Size, and Firm Size significantly affects ROA. Tax planning also has a direct effect on profitability, while Firm Size partially mediates this relationship. These results demonstrate that tax planning enhances profitability not only through increased after-tax income but also through asset accumulation that strengthens the firm’s capacity to generate returns. The study concludes that tax planning functions as a strategic financial instrument that supports both corporate growth and profitability when implemented within legal and sustainable boundaries.